Between positivism and narrativism in Polish methodology of history - Brzechczyn, Krzysztof (Historein, 2013)
<!--[if gte mso 9]> Normal 0 21 false false false MicrosoftInternetExplorer4 <![endif]--> This paper has two main purposes. Its primary purpose is to present the reception of the discussion between positivism and narrativism in the Polish methodology of history. A secondary one is to paraphrase, using the notion apparatus of the idealisational theory of science, the issue of the accuracy of explanation. The article consists of six parts. In the first part, Hempel’s deductive-nomological (or covering-law) model of explanation is presented. In the second part, the main tenets and assumptions of the Poznań school of methodology are presented. The emergence of this school at the end of the 1960s delayed the popularisation of narrativism in Polish methodology of history. In the third part, the manifold reasons of this delayed reception are analysed. The popularization of narrativism was only possible in Poland after 1989, but it had a primarily imitative character. This outline of cultural and scientific context allows Chris Lorenz’s proposals (on the problem of the accuracy of explanation) to be put in a wider perspective (part four). Namely, this author describes “a theoretical historical debate” on the status of scientific laws and refers to a post-positivistic approach to science represented by Nancy Cartwright. This approach was to introduce new perspectives to the understanding of lawfulness. In the fifth part, the main assumptions and tenets (for example, modes of explanation) of another post-positivistic approach to science, namely the idealisational theory of science, are presented and compared with the Hempelian model of explanation. In the sixth part, Hempel’s explanatory sketch is paraphrased using the notion apparatus of the idealisational model of science which provides a solution in this theoretical framework, to the problem of accuracy of explanation posed by Lorenz. <!--[if gte mso 9]> <![endif]--><!--[if !mso]> <mce:style><! st1\:*{behavior:url(#ieooui) } --> <!--[endif] --><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:Standardowy; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman"; mso-ansi-language:#0400; mso-fareast-language:#0400; mso-bidi-language:#0400;} --> <!--[endif] -->